PENGARUH UKURAN PEMERINTAH, UMUR PEMERINTAH DAN OPINI AUDIT TERHADAP AUDIT DELAY - Satiman, Satiman; Ramdani, Edon; Suparmin, Suparmin (LPPM Universitas Ibnu Sina, 2024)
This study aims to analyze the effect of government size, government age, and audit opinion on audit delay. Data is downloaded through the official websites of BPK and DJPK. The population in this study are all provincial government entities in Indonesia for the period 2018 – 2022, totaling 34 provinces. In order to obtain a sample of 170 data. Sampling in this study used a purposive sampling technique. Namely sampling technique based on predetermined criteria. This type of research is descriptive with a quantitative approach. The analytical method used in this study is multiple linear regression analysis with the help of the eviews 9 program. The results of this study conclude that government size and government age have an effect on audit delay. Meanwhile, audit opinion has no effect on audit delay. And simultaneously government size, government age and audit opinion affect audit delay